Levels of heavy metals in corn and potato-based food products in district Nowshera Pakistan - Awan, Baber; Faisal, Muhammad Saleh; Khan, Hamna; Hameed, Nazim; Kashif, Lubna; Rehman, Kashif Ur (International Journal of Pathology, 2025)
Background: Heavy metal contamination in food products poses a major public health challenge worldwide, with children being particularly vulnerable due to their dietary habits and physiological sensitivity. Processed snacks, especially potato and corn-based varieties, are widely consumed in Pakistan, yet limited research has examined their safety in relation to heavy metal exposure. The objective of this study was to assess the toxicity of Lead (Pb), Cadmium (Cd), Chromium (Cr), and Copper (Cu) in branded and local snack products commonly sold in District Nowshera, Khyber Pakhtunkhwa, Pakistan.Methods: A cross-sectional study was conducted between December 2023 and May 2024 where Ninety-six samples of potato-based, corn-based, and mixed snacks were collected from three tehsils of District Nowshera using convenience sampling. After acid digestion, the concentrations of heavy metals were analyzed using Atomic Absorption Spectrophotometry (AAS). Results were compared against World Health Organization (WHO) and Food and Agriculture Organization (FAO) permissible limits. Data analysis was performed in SPSS v27, applying descriptive statistics, independent samples t-tests, and ANOVA.Results: Branded snacks dominated the market (55.2%) compared to local products (44.8%), with potato-based snacks being the most common (62.5%). Chromium was detected at the highest levels (mean 2.21 ± 0.05 mg/kg), exceeding WHO/FAO limits in all samples. The observed differences were significant between local and branded snacks for Cd (p = 0.001) and Cr (p = 0.013), with higher levels in local products. Lead and copper showed no significant differences between the two groups, though Pb levels approached permissible thresholds.Conclusion: The study underscores a concerning burden of heavy metals, particularly chromium, in snacks available in the markets of district Nowshera. Levels of lead also approaching unsafe limits. These observations highlight the urgent need for stricter regulatory enforcement, improved quality control measures, and public awareness campaigns